Some solutions of Vietnamese government to the impact of the global financial crisis - Mai, Thi Thanh Xuan (Đại học Kinh tế, 2016)
The global financial crisis started in the United States and blew all over the world in 2007 - 2009 was one of the worst crisis that impacted almost countries around the world. Vietnam although was not directly and quickly influenced by the crisis, most of its economic activities were passive and the economy growth even fell down. The Vietnamese government was very active to implement policies to react to the global financial crisis. They however were just temporary because they were only short term reactions or saved the economy of Vietnam from the crisis but they created neither sustainable, long term factors nor growth motivation for the economy itself and enterprises as well